Substituted judgment, procreative beneficence, and the Ashley treatment - Douglas, Thomas (Journal of medical ethics, 2015)
It is commonly thought that when a patient is unable to make a treatment decision for herself, patient autonomy should be respected by consulting the views of a patient surrogate, normally either the next-of-kin or a person previously designated by the patient.On one view, the task of this surrogate is to make the treatment decision that the patient would have made if competent. But this so-called ‘substituted judgment standard’ (SJS) has come in for has come in for a good deal of criticism recently. For instance, some question whether surrogates are able to reliably predict what the patient would have chosen. Others wonder how respecting a patient's counter-factual, rather than actual, choices is supposed to respect her autonomy. Such concerns have lead some to reject the SJS and argue for alternative characterisations of the role of surrogate decision-makers.In their feature article, John Phillips and David Wendler argue that the SJS does not need be rejected, but merely re-interpreted. On their favoured ‘endorsed life’ interpretation, surrogates ought to choose the treatment option that ‘best promotes the course of life that the patient valued’.1 This, they note, will often be the course of action that the patient would have chosen, but this will not always be so: in some cases, the patient would have irrationally chosen a treatment that in fact undermines the course of life he values.Four commentaries raise a number of objections to Phillips and Wendler's suggestion. However, one aspect of their proposal that escapes criticism is their view about which past values matter. They suggest that surrogates should make the treatment decision that best promotes the values of the patient's most recent competent self; the values the patient held just before becoming incompetent.This view strikes me as intuitively plausible, but it is difficult …